ANALISIS PENGARUH PENGGUNAAN ARTIFICIAL INTELLIGENCE PADA PEMBELAJARAN DI CYBER UNIVERSITY - Sitorus, Michael; Fadillah Murti, M. David (Universitas Siber Indonesia, 2024)
The research analyzes of the influence use Artificial Intelligence (AI) on Cyber University course. At education in AI has opened up a variety of new opportunities, including personalization of learning, increased teaching effectiveness, and optimization of academic management. The learning AI process becomes more adaptive and responsive to individual student needs, enabling the achievement of better learning outcomes. The use of technology also supports the development of interactive and interesting content, thereby increasing student motivation and engagement. Additionally, AI helps in big data analysis, which makes it easier for institutions to understand learning trends and student needs more accurately. However, implementing AI also presents challenges, such as technology dependency, privacy concerns, and the need for adequate technology infrastructure. The research shows that the integration of AI in education, although complex, offers significant benefits in improving the quality of education at the Cyber University. As many as 70% of regular students use AI, while 80% of employee class students rely on this technology in the learning process. In the AI ​​type category, 50% of regular students utilize ChatGPT as a tool, enhancing their learning experience. On the other hand, 65% of student employees rely on ChatGPT, proving that AI can maximize efficiency and productivity. The optimally utilizing the potential of AI, educational institutions can create a more innovative and effective learning environment, ready to face the challenges of the future.